Renewable energy source‐based multiarea AGC system with integration of EV utilizing cascade controller considering time delay. (24th July 2018) - Saha, Arindita; Saikia, Lalit Chandra
Summary: Automatic generation control of the unequal 3‐area system with diversified sources like small hydrothermal units in area‐1 and area‐2 and split shaft gas turbine thermal units in area‐3 with nonlinearity of generation rate constraint is explored. A cascade combination of integer order integral‐derivative with filter (IDN) and fractional order proportional derivative (FOPD) is considered as a secondary controller (IDN‐FOPD). The controller gains and other parameters are optimized using whale optimization algorithm. The performance of IDN‐FOPD controller has an upper hand when compared with some classical controllers like integral, proportional‐integral, and proportional‐integral‐derivative with filter (PIDN). Analyses reveal that the performance of a combination of IDN‐FOPD in area‐1 and PIDN controllers in other areas of system dynamics provides comparable results with IDN‐FOPD controllers in all areas. Thus, this combination of controllers is carried for further analyses. Even eigenvalue analysis has been performed for analyzing system stability. The impact of time delay on system dynamics is also studied. The impact of the inclusion of renewable source like a solar thermal power plant in area‐1 and electric vehicles in all areas provides better system dynamics in the presence of nonlinearity generation rate constraint and time delay. Sensitivity analysis reveals that controller gains and other parameters obtained at nominal conditions are robust to changes in variable solar insolation and demands no further reset.